The Battle of Łódź 1914: a chance to develop military heritage tourism in the metropolitan tourism region of Łódź - Bończak, Bartosz (Turyzm/Tourism, 2013)
Wars were and still are an intrinsic element in the history of mankind. They bring glory to the victorious, the bitterness of failure to the defeated, and always destruction and suffering to ordinary people, but at the same time they have had a great impact or even shaped the culture of societies. In many places all over the world, as well as in Poland, relics from wars, battlefields, fortifications and weapons are unique and an extraordinary attraction that might bring in tourists. This type of tourism is known as military heritage tourism. In Łódź and its vicinity there are many military sites that might potentially become an attraction. They are mostly related to the great but forgotten Battle of Łódź that took place during the Great War. However, are they attractive enough to create a tourism product?